1999
DOI: 10.1089/106161299320442
|View full text |Cite
|
Sign up to set email alerts
|

Successful PBSC Mobilization with High-Dose G-CSF for Patients Failing a First Round of Mobilization

Abstract: PBSC are the preferred source of stem cells for autologous transplantation. However, regardless of the mobilization procedure used, 10%-20% of patients fail to collect an adequate number to ensure prompt engraftment. There is as yet no standard mobilization procedure for patients who fail a first mobilization attempt. Here, we describe a highly efficient strategy to obtain an adequate number of stem cells for patients who failed a first mobilization attempt. Seventy-four patients with various hematologic malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 20 publications
2
63
1
Order By: Relevance
“…Positive results historically reported for high-dose G-CSF remobilization regimens 83,90 have not been notably strengthened or refuted by recent research. 23,93 Gazitt et al 83 reported that the administration of G-CSF 32 mg/kg s.c. daily for 4 days before apheresis and continuing until the last day of apheresis resulted in successful remobilization in 88% of 18 patients whose first mobilization attempt was unsuccessful; most of these patients had NHL.…”
Section: Mobilization Agent Mechanismmentioning
confidence: 90%
See 3 more Smart Citations
“…Positive results historically reported for high-dose G-CSF remobilization regimens 83,90 have not been notably strengthened or refuted by recent research. 23,93 Gazitt et al 83 reported that the administration of G-CSF 32 mg/kg s.c. daily for 4 days before apheresis and continuing until the last day of apheresis resulted in successful remobilization in 88% of 18 patients whose first mobilization attempt was unsuccessful; most of these patients had NHL.…”
Section: Mobilization Agent Mechanismmentioning
confidence: 90%
“…72,82 When G-CSF alone is used for stem cell mobilization, it is administered at doses ranging from 10 mg/kg s.c. daily to 32 mg/kg s.c. daily, beginning at least 4 days before the first apheresis session and continued until the last apheresis session. 65,83 After transplantation, the median time to granulocyte engraftment has been reported to be 11 days, and plt engraftment has been reported to be B11-14 days. 27,28 Mobilization with G-CSF is generally well tolerated; common AEs are bone pain, headache, anemia and decreased plt counts.…”
Section: Mobilization Agent Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…Peripheral blood mononuclear cell apheresis collected from a MM patient mobilized with 6 g/m 2 of cytoxan plus 250 g/m 2 of GM-CSF 39 were stained for stem cell markers (CD34-PE and CD45-FITC) and sorted for CD34 + /CD45 dim stem cells as described in the Methodology section. This particular patient had a total of 8.6% stem cells.…”
Section: Figurementioning
confidence: 99%